Alkaline phosphatase combined with γ-glutamyl transferase is an independent predictor of prognosis of hepatocellular carcinoma patients receiving programmed death-1 inhibitors - Xu, Lei; Chen, Lin; Zhang, Bin; Liu, Zhicheng; Liu, Qiumeng; Liang, Huifang; Chen, Yifa; Chen, Xiaoping; Leng, Chao; Zhang, Bixiang (Frontiers in Immunology, 2023)
Background: Immunotherapy plays an increasingly critical role in the systemic treatment of HCC. This current study aimed to establish a novel prognostic predictor of Programmed death 1 (PD-1) inhibitor therapy in hepatocellular carcinoma (HCC) independent of Child-Pugh grade. Methods: Our study screened patients with HCC who received PD-1 inhibitors at Tongji Hospital Affiliated to Tongji Medical College of Huazhong University of Science and Technology from January 2018 to December 2020. ALG grade was determined by the patient's serum ALP and GGT levels before the initiation of PD-1 inhibitors. The endpoints of our study were overall survival (OS) and progression free survival (PFS). Follow-up ended at May 31, 2022. Results: Eighty- five patients (77 with Child‒Pugh grade A, 8 with Child‒Pugh grade B at baseline) were enrolled according to the inclusion criteria. Patients with Child‒Pugh grade A achieved longer PFS and OS than those with Child‒Pugh grade B. Patients with ALG grade 3 at baseline showed worse tumor response and poorer survival, and ALG grade could stratify patients with Child‒Pugh grade A into subgroups with significantly different prognosis. Conclusions: ALG grade, combining ALP and GGT, is a novel and readily available prognostic marker and the predictive effect of ALG grade on patient prognosis is independent of Child‒Pugh grade.